Diabetes and tuberculosis: a systematic review and meta-analyis of mendelian randomization evidence - Ivaan Pitua; Raafidha Raizudheen; Mark Muyanja; Joseph Nyero; Morrish Okello Obol (Diabetology & Metabolic Syndrome)
Abstract Background Tuberculosis (TB) and diabetes mellitus (DM) are global health challenges, each imposing significant morbidity and mortality. Observational studies suggest an increased TB risk in individuals with DM, yet causal relationships remain unclear due to potential confounding factors. Mendelian randomization (MR) offers a method to assess causality by leveraging genetic variants as instrumental variables, mitigating biases from confounding and reverse causation. This systematic review aimed to consolidate existing MR evidence on the causal link between DM (types 1 and 2) and TB. Methods A comprehensive search was conducted in PubMed, Embase, Google Scholar, and Web of Science, identifying MR studies investigating the causal association between DM and TB. Studies were screened based on pre-specified inclusion criteria and assessed for quality using the STROBE-MR guidelines. Data extraction focused on study characteristics, MR methodology, and causal effect estimates. A meta-analysis was conducted estimate the pooled odds ratios for association between T2DM and TB. Results Four MR studies met the inclusion criteria, spanning East Asian and European populations. Findings indicated a consistent causal relationship between DM (particularly type 2 diabetes) and increased TB risk, with odds ratios (OR) ranging from 1.07 to 1.24 (p < 0.05). The pooled odds ratio (OR) was 1.2172 (95% CI: 1.1101–1.3347, p < 0.0001), indicating a significant positive association between T2DM and TB. One study identified pleiotropic effects, suggesting potential genetic overlap in DM and TB susceptibility. No reverse causal association was observed, indicating that TB does not increase the risk of DM. Conclusion This review highlights a causal association between DM and TB, emphasizing the need for integrated screening and management of DM within TB control programs, particularly in high-burden regions. Future MR studies should include diverse populations to enhance generalizability and explore genetic mechanisms underlying this association.